Current situation of Financial Education in Young University Students of Villavicencio Colombia (GEON Journal (Management, Organizations and Business), 2018)
Financial education allows people to properly manage the resources and finances of their family members.In this regard, the OECD argues that "financial education is the process by which individuals acquire a better understanding of financial concepts and products and develop the necessary skills to make informed decisions, assess risks and financial opportunities, and improve their well-being" . (OECD, 2008). Therefore, this research work pursues the objective of measuring the financial education of university students in Villavicencio Colombia. An instrument composed of 18 items was applied, which allows to identify the knowledge that is possessed about financial education. Part of the results obtained shows us that, of the total population of students surveyed, the majority is not clear about the subject of financial education.
Keywords: Education; Credit; Savings; University; Villavicencio